Effect of heat ameliorative measures on the growth and physiological response ofbuffalo heifers during summer - VIJAYAKUMAR, P; PANDEY, H N; SINGH, MUKESH; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2011)
The present investigations were conducted to study the effect of sprinkling and fan on the growth and physiological response of buffalo heifers during summer (June 2004 to September 2004). Murrah buffalo heifers (18) between 15 and 30 months of age were divided into 3 equal groups based on age and body weight, viz. T1, control; T2, provided with only fan; and T3, provided with fan and sprinkling for 10 min at 2h interval. The average weight gain during the experimental period was highest in the T3 (61.67 kg) followed by T2 (56.67 kg) and T1 (54.17 kg). The average daily gain was maximum in T3 (501.36 g/day) followed by T2 (460.71g/day) and was least in T1 (440.38g/day). The difference in the rectal temperature between morning (9 AM) and afternoon (2 PM) of control group was significantly higher (0.34ºC) than T2 (0.22ºC) and T3 (0.13ºC). The difference in pulse rate from morning to afternoon was also significant in T1 (2.61 beats/min) when compared to T2 (2.29 beats/min) and T3 (1.31 beats/min). Similarly, the difference in the rate of respiration between morning and afternoon periods was significantly higher in T1 (4.48 counts/min) when compared to T2 (2.28 counts/min) and T3 (1.06 counts/min). Results indicated that provision of sprinkling and fan provided favourable macro-and micro-environment to the animals.